Loss of Ezh2 synergizes with JAK2-V617F in initiating myeloproliferative neoplasms and promoting myelofibrosis - Shimizu, Takafumi (J Exp Med, 2016)
Myeloproliferative neoplasm (MPN) patients frequently show co-occurrence of JAK2-V617F and mutations in epigenetic regulator genes, including EZH2. In this study, we show that JAK2-V617F and loss of Ezh2 in hematopoietic cells contribute synergistically to the development of MPN. The MPN phenotype induced by JAK2-V617F was accentuated in JAK2-V617F;Ezh2(−/−) mice, resulting in very high platelet and neutrophil counts, more advanced myelofibrosis, and reduced survival. These mice also displayed expansion of the stem cell and progenitor cell compartments and a shift of differentiation toward megakaryopoiesis at the expense of erythropoiesis. Single cell limiting dilution transplantation with bone marrow from JAK2-V617F;Ezh2(+/−) mice showed increased reconstitution and MPN disease initiation potential compared with JAK2-V617F alone. RNA sequencing in Ezh2-deficient hematopoietic stem cells (HSCs) and megakaryocytic erythroid progenitors identified highly up-regulated genes, including Lin28b and Hmga2, and chromatin immunoprecipitation (ChIP)–quantitative PCR (qPCR) analysis of their promoters revealed decreased H3K27me3 deposition. Forced expression of Hmga2 resulted in increased chimerism and platelet counts in recipients of retrovirally transduced HSCs. JAK2-V617F–expressing mice treated with an Ezh2 inhibitor showed higher platelet counts than vehicle controls. Our data support the proposed tumor suppressor function of EZH2 in patients with MPN and call for caution when considering using Ezh2 inhibitors in MPN.